Pengaruh Pemberlan Kapur Dolomlt dan Pupuk Daun terhadap Pertumbuhan Bawang Daun (Allium fistulosum L.) pada Tanah Gambut - Ira Marsary; Zuraida Titin Mariana; Ahmad Kurnain (Universitas Lambung Mangkurat, 2020)
Spring onion (Allium fistulosum L.) is a commodity that grows optimally on fertile, Loose soil, high organic matter content, and soil pH 6.5 - 7.5. Peat Lands contain very high organic matter, but soil fertility is low and soil conditions are very acidic. soil acidity can be reduced by ameliorant such as dolomite lime. Spring onion production is also influenced by nutrients that can be given through soil or Leaf fertilizer. This study aims to determine the effect of dolomite lime and Leaf fertilizer (gandasil D) on the growth of spring onion and peat soil pH. This research uses factorial completely randomized design. The first factor is dolomite lime and the second factor is Leaf fertilizer (gandasil D). The doses of ameliorant were 0 tons.ha-1 (A0), 3 tons.ha-1 (A1), 6 tons.ha-1 (A2). The doses of Leaf fertilizer 0 g.I-1 (B0), 2 g.I-1 (B1), 4 g.I-1 (B2). The results of this study indicate that the interaction of A2B1 treatment (6 tons ha-1 dolomite lime with 2 g.l-1 Leaf fertilizer) can increase plant height and the number of plant tillers in peat Lands. Giving of 6 tons.ha-1 dolomite lime can reduce the acidity of peat soil from pH 4.64 to 6.64 at the age of 30 days after planting, and from pH 4.64 to 6.92 at the age of 40 days after planting. soil acidity can be reduced in peat Lands by giving dolomite lime in stages, namely at the age of 5, 15, 25, and 35 days after planting for spring onion.